2021
DOI: 10.3389/fpsyg.2021.614816
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Implicit Cognitive Biases Through the Performing Arts

Abstract: The aim of the present research was to test whether involvement in a 14-days training program in the performing arts could reduce implicit biases. We asked healthy participants to complete an Implicit Association Test (IAT) to assess biased attitudes to physical illness in two separate sessions, before and after the training program. Two separate control groups matched by age, gender and educational level completed the two IAT sessions, separated by same number of days, without being involved in the training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In particular, CAM beliefs are often promoted by authorities in the field of medicine (Posadzki et al, 2012), which could make the information received against them less effective if it does not come from a source with the same level of authority. In this sense, it has been suggested that resistant biases toward unsubstantiated beliefs might be better tackled by combining both adequate information from reliable sources and a first-person experience to help such information to be integrated (García-Arch et al, 2021). All these suggestions should be examined in future research in order to understand the differential effect of DI on different types of pseudoscience beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CAM beliefs are often promoted by authorities in the field of medicine (Posadzki et al, 2012), which could make the information received against them less effective if it does not come from a source with the same level of authority. In this sense, it has been suggested that resistant biases toward unsubstantiated beliefs might be better tackled by combining both adequate information from reliable sources and a first-person experience to help such information to be integrated (García-Arch et al, 2021). All these suggestions should be examined in future research in order to understand the differential effect of DI on different types of pseudoscience beliefs.…”
Section: Discussionmentioning
confidence: 99%